Enhanced mechanical properties and tribological performance of anodic oxide coating by using thermal power plant waste material - Mustapar, Norliyana; Liza, Shahira; Fukuda, Kanao; Mat Tahir, Noor Ayuma; Ishimatsu, Jun; Yaakob, Yazid; Othman, Intan Sharhida (Elsevier Ltd, 2024)
Numerous researchers have dedicated their efforts to exploring the utilization of industrial waste, specifically fly ash (FA), as a reinforcement for developing economical composites and minimizing ecological pollution problems. FA consists of multiple phases, including quartz (SiO2) and mullite (3Al2O3·2SiO2), which can significantly enhance the mechanical properties of materials. In tribological applications, incorporating FA into surface coatings can offer a cost-effective alternative to enhance surface properties. Meanwhile, the usage of FA and its difference from other commercial ceramics (e.g., SiO2) is still unknown. Thus, the present study aims to clarify the role of FA and factors that contribute to improving mechanical properties and tribological performance with commercial SiO2 as a comparison using electrochemical anodization. The growth mechanism was investigated by varying the anodizing times while maintaining a constant (100 g/L FA) in the electrolyte for the first phase. Meanwhile, the mechanical and tribological properties of different reinforcement content (0, 10, 50, and 100 g/L) were determined for the second phase. Then, evaluations were conducted on the surface morphology, chemical composition, surface hardness, and tribological properties. The results revealed that growth of oxide coating was initiated within the first 5–10 min by forming the barrier layer. Pores began to appear visibly after 30 min of anodizing time, while the complete formation of porous anodic oxide coating was achieved at 60-min with pores dimension (width: 30.75 ± 14.45 μm and depth: 13.4 ± 6.43 μm). Interestingly, 100 g/L of FA-reinforced anodic oxide coating demonstrated lower surface roughness (4.08 ± 0.41 μm), higher surface hardness (444.4 ± 8.63 HV), lowest coefficient of friction (COF) (0.46), and low wear rate (reduction almost 31.8 %) compared to 100 g/L of commercial SiO2 reinforced anodic oxide coating. The electrophoretic deposition effect, combined with the quartz (SiO2) and mullite (3Al2O3·2SiO2) phase structure, enhances mechanical properties and tribological performance.